Fluctuation Characteristic Analysis on Scraper Chain Transmission System - Jixin Wang; Junxia Li; Yuan Wang (Jixie chuandong)
To analyze the speed and acceleration fluctuation characteristics of the scraper chain transmission system during the meshing process, a double-sided contact fluctuation model is constructed, the correctness of the model is verified by experiments. The relationship between acceleration fluctuation and tension fluctuation is obtained by analyzing the strain signal and acceleration signal. The virtual prototype of the scraper chain system is established by using Adams software and the dynamics simulation is carried out. The influences of different driving modes, working inclinations and laying lengths on the fluctuation of the scraper chain are explored and the analytical results could provide a reference for reasonable design of the meshing drive mode between sprocket and scraper chain.